Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.5194/angeo-22-2849-2004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solar and magnetic activity on VHF scintillations near the equatorial anomaly crest

Abstract: Abstract. The VHF amplitude scintillation recorded during the period January 1991 to December 1993 in the declining phase of a solar cycle and April 1998 to December 1999 in the ascending phase of the next solar cycle at Varanasi (geogr. lat.=25.3 • , long. =83.0 • , dip=37 • N) have been analyzed to study the behavior of ionospheric irregularities during active solar periods and magnetic storms. It is shown that irregularities occur at arbitrary times and may last for <30 min. A rise in solar activity increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 29 publications
2
22
1
Order By: Relevance
“…However, the dependence of the first occurrence of low latitude plasma bubbles on local time is at its maximum at 23:00 LT, and most plasma bubble events last for <45 min. It indicates that the duration of plasma bubbles becomes greater as one approaches the equator (Chandra et al, 1993;Singh et al, 2004). In addition, a time delay of about 3 h exists between the first occurrence time of equatorial and low-latitude plasma bubbles.…”
Section: Statistical Resultsmentioning
confidence: 99%
“…However, the dependence of the first occurrence of low latitude plasma bubbles on local time is at its maximum at 23:00 LT, and most plasma bubble events last for <45 min. It indicates that the duration of plasma bubbles becomes greater as one approaches the equator (Chandra et al, 1993;Singh et al, 2004). In addition, a time delay of about 3 h exists between the first occurrence time of equatorial and low-latitude plasma bubbles.…”
Section: Statistical Resultsmentioning
confidence: 99%
“…Then, the storm presented a slow recovery phase that took more than 68 h. Previous studies have shown occurrence of postmidnight scintillation activity when the maximum of the main phase of the storms begins at midnight to dawn local time sector. According to Singh et al (2004) the chance of occurrence increases if the D st index is below À100 nT. This may be expected to be the case here for the storm of 5 November, in which SYM-H index is well below À300 nT.…”
Section: The Effects Of Different Types Of Storms On Scintillationsmentioning
confidence: 88%
“…According to Aarons (1991) the ring current (as seen by the D st index) may be a controlling factor in the generation of F-region irregularities. Recent studies have followed the Aarons' method to study geomagnetic storm effects on the generation or inhibition of F-layer irregularities, such as Kumar and Gwal (2000), Biktash (2004), Singh et al (2004) and Shang et al (2008). The advantage in the use of the SYM-H index is its 1-min time resolution which provides more precisely the time occurrence of the SCs, the maximum negative values of the horizontal component of geomagnetic field and the initial-to-main and recovery phase duration of the storms.…”
Section: Geomagneticallymentioning
confidence: 99%
“…The scintillation at Varanasi predominantly is observed in the pre-midnight periods in small patches with duration < 30 minutes (Singh and Singh 1997;Singh et al 2004). VHF scintillation data recorded during daytime for the period January 1991 to December 1993 in the declining phase of solar cycle and April 1998 to December 1999 in the ascending phase of the next solar cycle as well as recent year of January 2008 to December 2008 have been analyzed in this study.…”
Section: Experimental Observations and Data Analysismentioning
confidence: 99%
“…The scintillation index in dB has been scaled manually every 15 minutes by measuring peak-to-peak P max -P min excursion in dB and using a calibration chart and conversion chart (Whitney et al 1969), where 1 dB = 12% scintillation index, P max is the power amplitude of the third peak-to-peak down from the maximum excursion and P min is the power amplitude of the third level up from the minimum excursion. The similar method of analysis was adopted by All India Coordinated Program of Ionospheric and Thermospheric Studies (AICPITS) of Department of Science, Government of India Kumar et al 2000;Singh et al 2004Singh et al , 2006Vijayakumar et al 2007). Typical examples of daytime scintillations recorded at low latitude station Varanasi are shown in figure 1.…”
Section: Experimental Observations and Data Analysismentioning
confidence: 99%